Galaxy evolution and radiative properties in the early universe: Multi-wavelength analysis in cosmological simulations. Issue Volume 15:Issue S352(2019) (June 2019) - Arata, Shohei; Yajima, Hidenobu; Nagamine, Kentaro; Li, Yuexing; Khochfar, Sadegh
Abstract: Recent observations have successfully detected UV or infrared flux from galaxies at the epoch of reionization. However, the origin of their radiative properties has not been fully understood yet. Combining cosmological hydrodynamic simulations and radiative transfer calculations, we present theoretical predictions of multi-wavelength radiative properties of the first galaxies at z = 6–15. We find that most of the gas and dust are ejected from star-forming regions due to supernova (SN) feedback, which allows UV photons to escape. We show that the peak of SED rapidly shifts between UV and infrared wavelengths on a timescale of 100 Myr due to intermittent star formation and feedback. When dusty gas covers the star-forming regions, the galaxies become bright in the observed-frame sub-millimeter wavelengths. In addition, we find that the escape fraction of ionizing photons also changes between 1–40% at z > 10. The mass fraction of H ii region changes with star formation history, resulting in fluctuations of metal lines and Lyman-α line luminosities. In the starbursting phase of galaxies with a halo mass ∼10 11 Mȯ (10 12 Mȯ ), the simulated galaxy has L [OIII ] ∼ 10 42 (10 43 ) erg s −1, which is consistent with the observed star-forming galaxies at z > 7. Our simulations suggest that deep [Cii ] observation with ALMA can trace the distribution of neutral gas extending over ∼20 physical kpc. We also find that the luminosity ratio L [OIII ] / L [CII ] decreases with bolometric luminosity due to metal enrichment. Our simulations show that the combination of multi-wavelength observations by ALMA and JWST will be able to reveal the multi-phase ISM structure and the transition from starbursting to outflowing phases of high- z galaxies.